PENGARUH PROFITABILITAS PERUSAHAAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY - Ibrahim Musa; Yulius Gessong Sampeallo; Feni Nur Rahmawati (Politeknik Negeri Samarinda, 2020)
This study aims to determine (1) the effect of ROA (Return On Assets) on Corporate Social Responsibility (CSR), (2) the effect of ROE (Return On Equity) on Corporate Social Responsibility (CSR), (3) the effect of NPM (Net Profit Margin) ) on Corporate Social Responsibility (CSR), and (4) the simultaneous influence of ROA, ROE, NPM on Corporate Social Responsibility (CSR). The analytical method used in this study is multiple regression analysis. A sample of 22 companies was obtained from purposive sampling.The results show that (1) ROA has a significant effect on Corporate Social Responsibility. (2) ROE has a non-significant effect on Corporate Social Responsibility. (3) NPM has a non-significant effect on Corporate Social Responsibility. Keywords: ROA, ROE, NPM, CSR